Pengaruh Dana Desa terhadap Kesenjangan Indeks Pembangunan Manusia Wilayah Desa Kota di Indonesia: Institut Pertanian Bogor - Artha Graciela Pandiangan; Dominicus Savio Priyarsono; Mutiara Probokawuryan (IPB University, 2021)
The development gap is still an important issue. This can be seen in one of the goals in the framework of reference for the development of countries in the world which is formulated in the Sustainable Development Goals (SDGs). One form of inequality that often occurs in the region is the human development gap. The gap in human development in rural and urban areas causes a welfare gap. The gap in human development can be approached from the indicators of the human development index. The Village Fund distribution program is one of the efforts made by the government to reduce the number of development gaps in each region. This study aims to analyze the effect of village funds on the urban-rural human development gap in Indonesia for the 2015-2019 period. The analytical method used is descriptive analysis and panel data analysis. The results showed that the village fund program had a negative effect on the gap in Indonesia's human development, which was represented by life expectancy, the gap in average length of schooling, and the gap per capita in rural and urban areas in Indonesia.